Opening eyes to therapeutic perspectives of bioactive polyphenols and their nanoformulations against diabetic neuropathy and related complications. (3rd April 2021) - Khursheed, Rubiya; Singh, Sachin Kumar; Wadhwa, Sheetu; Gulati, Monica; Kapoor, Bhupinder; Awasthi, Ankit; Kr, Arya; Kumar, Rajan; Pottoo, Faheem Hyder; Kumar, Vijay; Dureja, Harish; Anand, Krishnan; et al.
ABSTRACT: Introduction : Diabetic neuropathy (DN) is one of the major complications arising from hyperglycaemia in diabetic patients. In recent years polyphenols present in plants have gained attention to treat DN. The main advantages associated with them are their action via different molecular pathways to manage DN and their safety. However, they failed to gain clinical attention due to challenges associated with their formulation development such as lipophilicity, poor bioavailability, rapid systemic elimination, and enzymatic degradation. Area covered : This article includes different polyphenols that have shown their potential against DN in preclinical studies and the research carried out towards development of their nanoformulations in order to overcome aforementioned issues. Expert opinion : In this review various polyphenol based nanoformulations such as nanospheres, self-nanoemulsifying drug delivery systems, niosomes, electrospun nanofibers, metallic nanoparticles explored exclusively to treat DN are discussed. However, the literature available related to polyphenol based nanoformulations to treat DN is limited. Moreover, these experiments are limited to preclinical studies. Hence, more focus is required towards development of nanoformulations using simple and single step process as well as inexpensive and non-toxic excipients so that a stable, scalable, reproducible and non-toxic formulation could be achieved and clinical trials could be initiated.